2019
DOI: 10.1016/j.jare.2019.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Survival of occlusal ART restorations using high-viscosity glass-ionomer with and without chlorhexidine: A 2-year split-mouth quadruple-blind randomized controlled clinical trial

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
(33 reference statements)
2
5
0
1
Order By: Relevance
“…Glass ionomer shows lower adhesion when compared to other adhesive materials, such as composite resin. 42 Although there are studies showing its satisfactory clinical longevity, 43 glass ionomer does not appear to be ideal for use in load-bearing areas or restorations involving multiple surfaces. 44 In addition, this review did not consider all aspects of the restorative procedure, as there was a lack of information about the conditions under which the restorations were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Glass ionomer shows lower adhesion when compared to other adhesive materials, such as composite resin. 42 Although there are studies showing its satisfactory clinical longevity, 43 glass ionomer does not appear to be ideal for use in load-bearing areas or restorations involving multiple surfaces. 44 In addition, this review did not consider all aspects of the restorative procedure, as there was a lack of information about the conditions under which the restorations were performed.…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the antimicrobial ability of GIC, few authors have incorporated chlorhexidine (CHX) into it [10][11][12][13][14][15]. However, the survival of conventional and or CHX modified GIC depends upon cavity size, number of surfaces involved, the experience of the operator, and isolation techniques used during the restorative procedure [16][17][18][19][20][21][22][23][24]. The cavity size Appl.…”
Section: Introductionmentioning
confidence: 99%
“…The larger restorations have greater failure rates due to recurrent caries, fracture of restorations, and the larger surface area leading to restoration failure [15,17,24]. Previously, several studies [18,21,24,[26][27][28] have focused on the survival of single surface ART restorations without considering the influence of cavity size. Although it is reported that physical properties are not affected in CHX modified GIC, [11,14,15] the survival of the same has been tested by a limited number of studies [10], especially in the primary dentition [15,24].…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts have been made to improve its properties, such as the inclusion of metallic particles 22 , composite resins 23,24 , microfibers 25 , among others. Also, additives like chlorhexidine and zinc are used to improve antimicrobial GICs properties 26,27 . The antimicrobial properties of zinc oxide (ZnO) are extensively studied, which are improved by surface area, particle size, morphology, and surface charge 28,29 .…”
Section: Introductionmentioning
confidence: 99%